In Vitro Antioxidative Evaluation of α- and β-Carotene, Isolated from Crude Palm Oil - Surashree Sen Gupta; Mahua Ghosh (Journal of Analytical Methods in Chemistry)
The present work describes the isolation of α- and β-carotene from crude palm oil and their antioxidant potential in an in vitro model. Pure product was isolated by the method adopted. Antioxidant activities of the isolated α- and β-carotene were analyzed in five different concentrations of 0.001, 0.005, 0.01, 0.05, and 0.1% (w/v). From the several assays conducted, an observation was made that the antioxidant activity of the product shifted between antioxidant and prooxidant effects depending on the concentration and the system analyzed. The metal chelation, DPPH radical scavenging, and superoxide scavenging activities showed almost similar results in terms of high activity at lowest concentrations. ABTS-scavenging activity was displayed only by a particular antioxidant concentration of 0.1%. Lipid peroxidation assay pronounced the activity of 0.1% antioxidant in inhibiting oxidation of sensitive bioactive lipids. In vitro antidenaturation test again specified the efficacy of low concentrations in preventing protein denaturation. Through this study a definite dosage formulation for consumption of carotenoids is being proposed which will enhance health promotion and prevent chronic diseases when taken as fortified foods or dietary supplements.